Control of foliar pathogens of spring barley using a combination of resistance elicitors - Walters, Dale R.; Havis, Neil D.; Paterson, Linda; Taylor, Jeanette; Walsh, David J.; Sablou, Cecile (Frontiers in Plant Science, 2014)
The ability of the resistance elicitors acibenzolar-S-methyl (ASM), β-aminobutyric acid (BABA), cis-jasmone (CJ), and a combination of the three products, to control infection of spring barley by Rhynchosporium commune was examined under glasshouse conditions. Significant control of R. commune was provided by ASM and CJ, but the largest reduction in infection was obtained with the combination of the three elicitors. This elicitor combination was found to up-regulate the expression of PR-1b, which is used as a molecular marker for systemic acquired resistance (SAR). However, the elicitor combination also down-regulated the expression of LOX2, a gene involved in the biosynthesis of jasmonic acid (JA). In field experiments over three consecutive years, the effects of the elicitor combination were influenced greatly by crop variety and by year. For example, the elicitor combination applied on its own provided significant control of powdery mildew (Blumeria graminis f.sp. hordei) and R. commune in 2009, whereas no control on either variety was observed in 2007. In contrast, treatments involving both the elicitor combination and fungicides provided disease control and yield increases which were equal to, and in some cases better than that provided by the best fungicide-only treatment. The prospects for the use of elicitor plus fungicide treatments to control foliar pathogens of spring barley in practice are discussed.